THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF E-WOM ON REPURCHASE INTENTION (STUDY ON LUSI & PAKAN BALI CUSTOMERS) - Putu Adistya Priyanka Surya; Putu Yudi Setiawan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Repurchase intention is a commitment held by consumers to repurchase the same product due to the positive impression of the product or service. The aim of this research is to analyze and explain the influence of E-WOM on repurchase intention and the role of customer satisfaction in mediating the influence of E-WOM on repurchase intention at Lusi & Pakan Bali. The sample in this study consists of 96 respondents, selected based on purposive sampling technique. Data collection was conducted using questionnaires. The analysis method used is structural equation modeling based on partial least squares (SEM- PLS). The results show that E-WOM has a positive and significant influence on repurchase intention, E-WOM has a positive and significant influence on customer satisfaction, customer satisfaction has a positive and significant influence on repurchase intention, and customer satisfaction is able to partially mediate the influence of E-WOM on repurchase intention. The implication of this research is that Lusi & Pakan Bali can consider E-WOM and customer satisfaction in formulating policies to pay attention to or enhance electronic word of mouth, thereby increasing customer satisfaction which can drive the creation of repurchase intention.